Is there a common pattern to integrate multiple management systems? A comparative analysis between organizations in Greece and Spain. (10th May 2017) - Bernardo, Merce; Gianni, Maria; Gotzamani, Katerina; Simon, Alexandra
Abstract: The integration of management systems has been mainly studied considering the process within organizations and also comparing the implementation among organizations in the same country. Scarce research has been done comparing the process among organizations in different countries. Thus, the main aim of this study is to analyze and compare the implementation of the integrated management systems between organizations located in two countries, Greece and Spain, which have different ISO 9001 and ISO 14001 certification rates. A qualitative method has been applied. Six case studies are presented, three per country, to analyze the aspects of the process and comparing both implementation processes. All organizations have, at least, the ISO 9001 and the ISO 14001 management systems certification. The integration aspects studied are: strategy, methodology, level, audits, benefits and difficulties. The findings, although exploratory, show that the differing integration aspect among the analyzed organizations is the audits both internal and external. Greek organizations achieve higher levels of internal audits integration rather than external but these levels are lower compared to the audits integration level of the Spanish organizations. The other aspects analyzed followed a similar pattern, i.e., the majority of organizations implement first the quality management system and then the environmental, common elements analysis is the main methodology applied, the level reported show a tendency to full integration and benefits and difficulties highlighted are also similar. In addition to these results, aspects that could condition the process are proposed for future research, such as: certification rates, top management commitment, internalization of management systems, external auditors' experience, state support and their impact on sustainability. Implications for academia, organizations and certification bodies are also presented. Although the integration of management systems has been analyzed in the literature, this is one of the first studies comparing organizations in countries with different certification rates and proposing specific factors conditioning the process for future research. Graphical abstract: Highlights: MSs integration internal aspects follow the same pattern in different countries. MSs certification rates condition external audits integration. External auditors' skills condition external audits integration. Factors conditioning the integration process have been identified.